Multiple Microinvasion Foci in Ductal Carcinoma In Situ Is Associated With an Increased Risk of Recurrence and Worse Survival Outcome - Jing Si; Jing Si; Rong Guo; Huan Pan; Xiang Lu; Zhiqin Guo; Chao Han; Li Xue; Dan Xing; Wanxin Wu; Caiping Chen; Caiping Chen (Frontiers in Oncology, 2020)
BackgroundDuctal carcinoma in situ with microinvasion (DCISM) was defined as one or more foci of invasion beyond the basement membrane within 1 mm. The size of primary lesion is associated with axillary status and prognosis in patients with invasive breast cancer; thus, it is of interest to determine whether multiple foci of microinvasion are associated with a higher risk of positive axillary status or worse long-term outcomes in patients with DCISM.MethodsThis study identified 359 patients with DCISM who had undergone axillary evaluation at our institute from January 2006 to December 2015. Patients were categorized as one focus or multiple foci (≥2 foci) according to the pathological results. Clinicopathological features, axillary status, and disease-free survival rate were obtained and analyzed.ResultsOf 359 patients, 233 (64.90%) had one focus of microinvasion and 126 (35.10%) had multiple foci. Overall, 242 (67.41%) and 117 (32.59%) patients underwent sentinel lymph nodes biopsy (SLNB) and axillary lymph nodes dissection (ALND), respectively. Isolated tumor cells were found in four (1.11%) patients and axillary metastasis rate was 2.51%. Neither axillary evaluation methods (P = 0.244) nor axillary metastasis rate (P = 0.559) was significantly different between patients with one focus and multiple foci. In univariate analysis, patients with multiple foci tended to have larger tumor size (P < 0.001), higher nuclear grade (P = 0.001), and higher rate of lymphatic vascular invasion (P = 0.034). Also, the proportion of positive HER2 (P = 0.027) and Ki67 level (P = 0.004) increased in patients with multiple foci, while in multivariate analysis, only tumor size showed significant difference (P = 0.009). Patients with multiple foci were more likely to receive chemotherapy (56.35 vs 40.77%; P = 0.028). At median 5.11 years follow-up, overall survival rate was 99.36%. Patients with multiple microinvasive foci had worse disease-free survival rate compared with one-focus patients (98.29 vs 93.01%, P = 0.032).ConclusionEven though the numbers of microinvasion were different and patients with multiple foci of microinvasion tended to have larger tumor size, there was no higher risk of axillary involvement compared with patients with one focus of microinvasion, while patients with multiple microinvasive foci had worse DFS rate. Thus, DCISM patients with multiple foci of microinvasion may be the criterion for more aggressive local–regional treatment. Optimization of adjuvant therapy in DCISM patients is required.